Reactivity and Stability of Metalloporphyrin Complex Formation: DFT and Experimental Study - Rimadani Pratiwi; Slamet Ibrahim; Daryono H. Tjahjono (Molecules, 2020)
The interaction of three cationic porphyrins—meso-tetrakis (N-methylpyridinium-4-yl) porphyrin (TMPyP), meso-tetrakis (1,3-dimethylimidazolium-2-yl) porphyrin (TDMImP), and meso-tetrakis (1,2-dimethylpyrazolium-4-yl) porphyrin (TDMPzP)—with five heavy metals was studied computationally, and binding constants were calculated based on data obtained by an experimental method and compared. The reactivity and stability of their complexes formed with lead, cadmium, mercury, tin, and arsenic ions were observed in DFT global chemical reactivity descriptors: the electronic chemical potential (µ), chemical hardness (η), and electrophilicity (ω). The results show that M-TDMPzP has higher chemical hardness and lower electrophilicity compared to M-TMPyP and M-TDMImP, indicating the reaction of TDMPzP with metals will form a more stable complex. Specifically, Cd-TDMPzP complexes can stabilize the system, with a lower energy and electronic chemical potential, higher chemical hardness, smaller electrophilicity, and higher binding constant value compared to Pb-TDMPzP and Hg-TDMPzP. This result suggests that the interaction of the Cd2+ ion with TDMPzP will produce a stable complex.